Platelet kinetics in patients with chronic immune thrombocytopaenia treated with thrombopoietin receptor agonists. (27th January 2023) - Pravdic, Zlatko; Suvajdzic‐Vukovic, Nada; Djurdjevic, Predrag; Pantic, Nikola; Bukumiric, Zoran; Virijevic, Marijana; Todorovic‐Tirnanic, Mila; Thachil, Jecko; Mitrovic, Mirjana
Abstract: Introduction: Thrombopoietin receptor agonists (TPO‐RAs) increase platelet counts (PC) in the majority of patients with chronic immune thrombocytopaenia (ITP). Platelet kinetics study (PKS) might contribute to the understanding of mechanisms that lead to durable response. Objectives: To evaluate the effects of TPO‐RAs on PKS parameters in chronic ITP patients. Methods: Fifteen chronic ITP patients, aged 59 years [range: 22–84], female/male: 10/5, splenectomised 7/15, were treated with TPO‐RAs (eltrombopag/romiplostim: 11/4). Durable response was defined as PC ≥30 × 10 9 /L at 6 months. Autologous 111 Indium‐oxinate PKS was performed before and 5 months after TPO‐RAs initiation. Accordingly, platelet survival (PS), platelet turnover, production ratio and sequestration site were assessed. Results: Durable response was achieved in 13/15 of patients (eltrombopag/romiplostim: 10/3). Pre‐treatment parameters were: PC 10 × 10 9 /L [range: 1–110], PS 0.5 days [range: 0.1–1.7 (normal values: 7–10)], platelet turnover 30 857 Plt/μL/day [range: 944–103 500] and platelet production ratio 0.64 [range: 0.01–3.2 (normal values: 1 ± 0.2)]. Post‐treatment assessment showed significantly higher: PC 92.5 × 10 9 /L [range: 28–260, p = .001], PS 2.2 days [range: 0.1–3.6, p = .008], platelet turnover 70 213 Plt/μL/day [range: 2800–462 236, p = .02] and platelet production ratio 1.8 [range: 0.5–37.9, p = .011] compared to the pre‐treatment values. Platelet sequestration site altered in 3/15 treated with TPO‐RAs. Conclusions: TPO‐RAs could increase PC by simultaneous increasing of platelet production and decreasing of platelet destruction.